Physiopathology and Regulation of Factor XIII - Ichinose, Akitada (Thrombosis and Haemostasis, 2001)
Factor XIII is a plasma transglutaminase. Transglutaminases are at least 8 enzymes which cross-link a number of proteins. This type of reaction not only enhances the original functions of substrate proteins, but also adds new functions to them. Factor XIII in plasma is a tetramer (A2B2), and the A subunit contains the active site. Although transglutaminases are homologous, the nucleotide sequences in their 5’-flanking region differ significantly. Accordingly, transcription factors play a major role in the cell type-specific expression of each transglutaminase. A variety of missense and nonsense mutations, and deletions/insertions with or without out-of-frame shift/premature termination and splicing abnormalities have been identified in the genes for A and B subunits in factor XIII deficiency. In some cases, the mRNA level of the A or B subunit was severely reduced. Molecular and cellular bases have also been explored by expression experiments and by molecular modeling. In most cases, impaired folding and/or conformational change of the mutant A or B subunit leads to both intra- and extra-cellular instability, which is responsible for factor XIII deficiency.
Keywords: Transglutaminase; cross-linking; bleeding disorder; wound healing; molecular abnormality